Genome-Wide Association Study for the Identification of Genetic Variants Associated with Facial Skin Phenotypes - Rusma Yulita; Aswin, Yulia Ariani; Paramita, Rafika Indah (EKSAKTA: Berkala Ilmiah Bidang MIPA, 2024)
Facial skin phenotypes such as pigmentation, wrinkles, and lentigines are determined by genetics and environmental factors. The genetic factor is known as the basic formation of facial skin phenotype variations in different populations. Genetic variations can be used as an approach to understanding genetic influences on the phenotype of interest and may influence molecular and cellular mechanisms. Genome wide-association study (GWAS) is used to identify common genetic variants associated with quantitative traits or complex human diseases. GWAS reveals a single phenotypic which is associated with a large number of SNPs and provides statistical information as significant SNPs. To perform GWAS analysis, bioinformatics tools are used as a rapid genetic data computation for large biological datasets which can report gene/locus with a related biological function viewed in silico. In this review, we summarize a common step-by-step workflow to conduct GWAS using bioinformatics analysis. The step-by-step workflow helps researchers understand how to identify SNPs with phenotypes of interest using bioinformatics approaches. Then, we explore common SNP and gene of facial skin phenotypes from several populations originating from various countries that can provide insights into the genetic contributions to facial skin phenotypes.